2016
DOI: 10.3390/agriculture6020015
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors That Influence Use of ICT in Agricultural Extension in Southern Africa

Abstract: Farmbook is a novel information communication technology (ICT) tool for agricultural extension that is currently being field tested by the Catholic Relief Services (CRS) in Southern and East Africa. Farmbook enables extension agents to assess productivity and profitability of farming enterprises in a faster and more reliable manner, so as to increase farmer incomes and achieve food security. This study looked at the relationship between challenges faced by extension agents testing the Farmbook application and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…Possibly this can be explained by the fact that mobile phones are more versatile than the internet emails and websites hence can be used to access several services such as telecommunication services. Tata and McNamara [16] asserted that ICTs supplement rather than replace traditional extension methods. Further, the use of ICTs by extension agents' has been documented to result into personal benefits and increased professional productivity and sustained traditional interaction between farmers and agents.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly this can be explained by the fact that mobile phones are more versatile than the internet emails and websites hence can be used to access several services such as telecommunication services. Tata and McNamara [16] asserted that ICTs supplement rather than replace traditional extension methods. Further, the use of ICTs by extension agents' has been documented to result into personal benefits and increased professional productivity and sustained traditional interaction between farmers and agents.…”
Section: Discussionmentioning
confidence: 99%
“…Also, women show more interest in knowing about mobile technologies and report a feeling of empowerment in response to information. Likewise, Tata and McNamara (2016) analyzed the use and effectiveness of Farmbook in Southern Africa, a farm technology application available for both mobile devices and desktop, and found that although women face more farmlevel challenges in applying the knowledge they gain from Farmbook, they also report lower occurrences of technical challenges in using the application itself (Tata and McNamara 2016).…”
Section: Mobile Phones Food Security and Agricultural Outcomesmentioning
confidence: 99%
“…• low level of education, such as the issue of the level of illiteracy [3], lack of interest in reading [12], farmers not active in finding information [4], and educational qualification related to ability to operate the internet and applications [6],…”
Section: B the Capacity Of Farmers In Using Ictmentioning
confidence: 99%
“…Another research, in India, farmers access information on agricultural inputs and market prices through television, radio, mobile phones, and the internet [5]. Southern Africa developed farmbook, ICT application to help farmers plan their businesses, assess productivity, and profitability of their farming enterprise [6]. Some results from that research show that ICT is very beneficial to the society particularly farmers to access information.…”
Section: Introductionmentioning
confidence: 99%